Psikologi Atlet Junior Sian Soor Tenis Lapangan Dalam Pertandingan - Abdul Muhaemin M, Ince; Marsuki; Syaiful, Andi; Sari Kardi, Ipa; Ibrahim (Indonesian Journal of Physical Education and Sport Science, 2024)
Studi purpose: As an athlete who has a demand to excel when competing, anxiety in athletes becomes one of the conditions that athletes often experience which affects the athlete's performance in facing the match. One of the mental factors that trigger athletes' psychology is anxiety, self-confidence, and resilience factors. This study aimed to determine the level of anxiety, self-confidence, and resilience of Sian Soor junior athletes in the sport of tennis. Materials and methods: This type of research was descriptive quantitative, which is to see a description of the psychological aspects of junior athletes Sian Soor tennis court. The research location was conducted at the Sian Soor tennis Mayor of Jayapura City Papua. The population in this study were all junior athletes Sian Soor Jayapura City Papua involving 25 people from the age group 10 to 18 years. The sample was taken based on random sampling with a total of 18 athletes. The instruments used in data collection were anxiety, self-confidence, and resilience instruments. Results. Based on data analysis from 18 athletes the results that the anxiety aspect was very high (5.56%), high (22.22%), moderate (44.44%), and low (27.78%). Aspects of confidence were very high (5.56%), high (16.67%), medium (61.11%), and low (16.67%). The resilience aspect was high (16.67%), medium (66.67%), and low (16.67%). Conclusions. Based on the results obtained in this study, it is concluded that Junior Sian Soor athletes in Jayapura City Papua on the dominant anxiety aspects of the moderate category, aspects of self-confidence in the moderate category, and resilience in the moderate category. therefore it is suggested to the coach to provide interventions in the form of mental training, especially to increase self-confidence and resilience, so that the degree of anxiety competing can be minimized.